Navigating Hormonal Disruptions in Neuroleptic Drug Therapy: Current Insights and Obstacles - Gowtham, HB; Tiwari, Prashant; Jaiswal, Vaivhab (Current Psychopharmacology, 2025)
Neuroleptic drug therapy, used to manage psychotic disorders, often induces hormonal disruptions that can impact patient health and treatment outcomes. This review explores the relationship between neuroleptic medications and the endocrine system, highlighting current insights and clinical challenges. Antipsychotic drugs often elevate prolactin levels, leading to hyperprolactinemia, which manifests as galactorrhea, amenorrhea, and sexual dysfunction. These medications can also alter insulin and glucagon levels, contributing to metabolic syndromes, like type 2 diabetes and insulin resistance. Disruption of thyroid hormone homeostasis can result in hypothyroidism or hyperthyroidism, exacerbating psychiatric symptoms. Moreover, neuroleptic drugs affect growth hormone and adrenal function, potentially causing weight gain and adrenal insufficiency. Understanding these hormonal side effects is crucial for developing treatment plans that mitigate adverse effects while optimizing psychiatric care. Despite advances in psychopharmacology, challenges remain in predicting individual patient responses and managing long-term endocrine complications. Current research underscores the need for routine endocrine monitoring in patients on neuroleptic therapy and exploring adjunctive treatments to counteract these side effects. Future studies should focus on elucidating the molecular mechanisms underlying these hormonal disruptions and developing targeted interventions to improve patient outcomes. This review provides an overview of the hormonal side effects of neuroleptic drugs, emphasizing the importance of interdisciplinary approaches in addressing the needs of patients with psychotic disorders.
Keywords: thyroid hormone